A study of the role of Saudi Higher Education institutions in promoting critical thinking among university students amidst the subtle cognitive reprogramming induced by social media - Alotaibi, Salman Sahud Raqi; Ismail, Sayed M. (Research Journal in Advanced Humanities, 2024)
Cognitive online effects greatly influence critical thinking, and Saudi Higher education institutions (HEIs) have been reassessing their approach to educating students on issues of critical thinking. While teaching methods to bolster CTS have been explored at the higher education level in many western universities, in Saudi Arabia, similar research is scarce, understudied, and theretofore uncorroborated. In Saudi Arabia, efforts to foster critical thinking skills (CTS), in the effective intervention of new media and critical reading instruction, have been caught in spirited controversies. This clarification is needed but not yet definitively addressed in the literature. Therefore, the present study aims to critically evaluate the role of the Saudi higher education institutions in promoting critical thinking among university and whether the Saudi universities could manage successful to combat intellectually the subtle cognitive reprogramming induced by the social media. Therefore, the present study relies on reflective and critical methodology through reviewing the previous studies tackling the incorporation of the critical into the University curricula. The methodology used in the current study is highly critical and insightful as it raised questions and suggests solution through reviewing numerous studies tacking the Saudi context which pertains to the Saudi institutions of the higher education awareness of the importance of the critical thinking, its incorporation into the curricula, the threats of the social media on the minds of the university studies. The study has reached a number of high invaluable findings, among the most important of which is that method of incorporating the critical thinking into university crucial is still ineffective and many instructors are not adequately trained to deliver the critical thinking content to their students’ minds.